Single-harmonic active power line conditioner for harmonic distortion control in power networks - Ramos-Carranza, Hugo A; Medina, Aurelio (IET power electronics, 2014)
In this contribution, a novel alternative concept and solution procedure for single-harmonic active power line conditioner (SHAPLC) planning is proposed to control voltage harmonic distortion in power networks. The development of the proposed solution concept, defined and detailed in this paper, is based on seeking a proper solution to practical situations, taking into account the particular harmonic distortion pattern and configuration of the power system in question. The location of the SHAPLC's, for each harmonic h of interest is determined through feasibility and sensitivity analysis. Once the best location for the SHAPLCs is known, the injection currents are determined by solving a non-linear programming algorithm. The usefulness and novelty of the SHAPLC planning methodology is illustrated with a case study, where results show its effectiveness to control the harmonic distortion in the power system. The solution procedure proposed in this contribution is aimed to achieve and assure individual harmonic distortion and total harmonic distortion indices meet recommended limits by Std-519 IEEE using SHAPLCs devices. According with revised literature, this goal has only been approached with certainty and sufficiency (not trial and error) by considering multiple injection currents at different harmonic frequencies from the selected bus.